Photochemical, Anatomical, and Growth Changes in Cassava Cultivars after Application of Post-Emergent Herbicides - Jania Claudia Camilo dos Santos; Renato Nunes Costa; Dayane Mércia Ribeiro Silva; Dougllas Ferreira da Rocha; Lennon Klédson dos Santos Silva; Rudieli Machado da Silva; Marcelo de Almeida Silva; Jessé Marques da Silva Júnior Pavão; José Vieira Silva (Agriculture, 2022)
Plants develop a series of adaptive mechanisms capable of tolerating the action of herbicides; however, little is known about the physiological mechanisms developed by cassava. The purpose of this research was to evaluate the influence of post-emergence herbicides on the physiological and anatomical characteristics of two cassava cultivars subjected to six herbicide treatments. The evaluations occurred at 0, 24, 48, 72, and 168 h after herbicide application. Herbicide application induced changes in the physiological and anatomical leaf profile. These changes were observed through the thickening of the leaf blade midrib caused by the herbicides fomesafen and fenoxaprop-p-ethyl in the Campinas cultivar. On the other hand, the leaves of the Sergipana cultivar showed a reduction in the thickness of the midrib tissues. Minor effects on cassava plants were observed with the herbicide fluazifop-p-butyl.